Bibliometric Studies In The Use Of Technology And Social Media For Marketing - Eka Yudhyani (International Journal of Management Research and Economics, 2025)
In order to gain a comprehensive view of marketing communications and understand the current research emphasis, this study evaluates the most relevant themes related to marketing communications through a bibliometric analysis using the keyword "marketing communications" as input. The Scopus database is used because it is considered ideal for bibliometric analysis. VOSviewer software is adopted as a bibliometric analysis tool to visualize the network of authors, countries, journals and keywords. An analysis conducted on 23 November 2022 found a total of 1,655 published documents from 2015 to 2022. The results showed that from 2015 to 2022 the number of publications had increased related to the theme of marketing communications. The United States is the country that has the most research benefits related to marketing communications. Keyword analysis shows that marketing communication studies in the last two years refer to marketing done through social media. It is considered more effective in advertising their products to consumers and is also a form of utilizing technology in marketing communications. The presented bibliometric analysis provides relevant information on the main themes of marketing communications and the benefits of social media and technological advancements.